IMPACT OF ANCHOR- BORROWERS’ PROGRAMME (ABP) ON RICE FARMING IN FEDERAL CAPITAL TERRITORY, ABUJA NIGERIA - Ejembi, I.; Umar, H.S.; Galadima, O.E. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study investigates the impact of Anchor Borrowers’ Programme on rice farming in the Federal Capital Territory Abuja, Nigeria. Multi-stage sampling technique was used to randomly select 357 respondents (162 beneficiaries and 195 non-beneficiaries). Data were collected using questionnaire. The data were analysed using descriptive statistics, Logistic regression model, Propensity Score Matching (PSM) and Gross Margin Analysis. The mean age of beneficiaries and non-beneficiaries were 37 and 49 years, respectively; 72.2% and 76.1% were male; 82.1% and 75% were married, respectively. Beneficiaries and non-beneficiaries on the average had farm size of 2 hectares approximately. The result of the logistic regression on determinant of participation in the ABP reveals that the model is statistically significant with pseudo-R-square of (0.563) indicating that about 56.3% of the variation in participation in the ABP explained by the socioeconomics characteristics considered in the model which are annual income with a coefficient of (4.198 at P<0.01), membership of association with a coefficient of (4.309 at P<0.01) and, farming experience with a coefficient of (0.247 at P<0.01), marital status with a coefficient of (0.803 at P<0.10), Age with coefficient of (-0.133 at P<0.01), Household size with a coefficient of (-0.244 at P<0.05), Farm size with a coefficient of (-0.313 at P<0.10), Access to extension has a coefficient of (-1.084 at P<0.10). PSM result on output reveals ATE of 18.1 bags significant (t=5.60, P<0.01). The study concludes that ABP impacted positively on rice yield of beneficiaries in the Federal Capital Territory Abuja, Nigeria. The study recommends that, anchor borrowers programme should remove/cut down bureaucratic bottleneck that discourage intending farmers from participating in the programme; more female farmers should also be enrolled by ABP to bridge the gap between male farmers who benefited from the programme and farm inputs and credit facilities must be provided to farmers in a timely manner to ensure prompt preparation for farming activities.